1988
DOI: 10.1177/003693308803300405
|View full text |Cite
|
Sign up to set email alerts
|

Sports Injuries as Seen at An Accident and Emergency Department

Abstract: We present certain characteristics of 1,000 consecutive patients who attended an Accident and Emergency Department (A&E) with an injury sustained as a result of sport. The majority of injuries occurred as a result of football. Sports injuries had a higher requirement of X-ray than general trauma patients. A minority were treated at the site of injury. A fifth of patients required no treatment or a simple dressing. Commonest treatment was a support bandage. Only 2% required immediate in-patient treatment. Those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…12 A survey of sport and recreational injuries presenting to a general practitioner clinic in Melbourne concluded that patients prefer to attend that setting for injury treatment if their injury is not too severe. 25 This is particularly the case if the practice is close to their home and there is not too long a wait for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A survey of sport and recreational injuries presenting to a general practitioner clinic in Melbourne concluded that patients prefer to attend that setting for injury treatment if their injury is not too severe. 25 This is particularly the case if the practice is close to their home and there is not too long a wait for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pickard et al 12 noted a significant limitation of injury data based on attendances at a hospital emergency department for describing sports injuries. Although such data systems may be reasonable for general community level sport, professional and elite level sports often employ adequate first aid and medical back up services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Football was found to be responsible for 50% of patients with sports injuries attending a Glasgow accident and emergency department 11 and 44.7% of eye injuries seen at a Glasgow eye casualty unit. 10 Football related eye injuries have been reported to be increasing in the United States since the 1970s, and this can be attributed to the rising popularity of the sport (soccer).…”
Section: Discussionmentioning
confidence: 99%
“…Two thirds of patients were male. The age groups that accounted for most injuries were 10-14 year olds (34.2%) and [15][16][17][18][19] year olds (16.7%).…”
Section: Gp Presentationsmentioning
confidence: 99%